Burning Mouth Syndrome. Update - Spanemberg, Juliana Cassol; de Rivera Campillo, Eugenia Rodríguez; Salas, Enric Jané; López, José López (The Journal of Dentists, 2014)
Burning Mouth Syndrome (BMS) is a chronic disorder that predominately affects middle-aged women in the postmenopausal period. The condition is distinguished by burning symptoms of the oral mucosa and the absence of any clinical signs. The etiology of BMS is complex and it includes a variety of factors. Local, systemic and psychological factors such as stress, anxiety and depression are listed among the possible causes of BMS. May sometimes be classified as BMS Type I, II or III. Although this syndrome is not accompanied by evident organic alterations and it does not present health risks, it can significantly reduce the patient’s quality of life. This study analyzes the available literature related to BMS, and makes special reference to its therapeutic management. The pages that follow will also discuss the diagnostic criteria that should be respected, etiological factors, and clinical aspects. We used the PubMed database and searched it by using the keywords “burning mouth syndrome”, “BMS and review”, and “burning mouth and review”, in the title or abstract of the publication. BMS treatment usually steers towards the management of the symptoms, however, the specific local factors that could play a significant role in worsening the oral burning sensation should be eradicated. The most widely accepted treatment options that show variable results include tricyclic antidepressants, benzodiazepines and antipsychotic drugs; nevertheless there are other therapies that can also be carried out. Professionals that work in the field of dentistry should formulate standardized symptomatic and diagnostic criteria in order to more easily identify the most effective and reliable strategies in BMS treatment through multidisciplinary research.